2016
DOI: 10.3389/fpls.2016.01856
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Leafed Lupin (Lupinus angustifolius) β1- and β6-Conglutin Proteins Exhibit Antifungal Activity, Protecting Plants against Necrotrophic Pathogen Induced Damage from Sclerotinia sclerotiorum and Phytophthora nicotianae

Abstract: Vicilins (7S globulins) are seed storage proteins and constitute the main protein family in legume seeds, particularly in narrow-leafed lupin (Lupinus angustifolius L.; NLL), where seven vicilin genes, called β1- to β7-conglutin have been identified. Vicilins are involved in germination processes supplying amino acids for seedling growth and plant development, as well as in some cases roles in plant defense and protection against pathogens. The roles of NLL β-conglutins in plant defense are unknown. Here the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 101 publications
1
22
0
Order By: Relevance
“…In general, these values are similar to the amount of protein present in soybeans (about 35%). The main proteins stored in the narrow, yellow, and white lupin seeds as well as in seeds of other legumes are globulins: γ-conglutin, β-conglutin (similar to vicilin), and α-conglutin (similar to legumin) (Lqari et al 2004;Sujak et al 2006;Duranti et al 2008;Foley et al 2015;Jimenez-Lopez et al 2016). Although the protein content (in mg/g of fresh weight) was comparable in the control and irrigated seeds, differences in the staining intensity of electrophoretically separated protein bands (especially the most strongly stained ones, which correspond to storage proteins) may indicate a possible difference in the quantitative proportions of particular types of storage proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these values are similar to the amount of protein present in soybeans (about 35%). The main proteins stored in the narrow, yellow, and white lupin seeds as well as in seeds of other legumes are globulins: γ-conglutin, β-conglutin (similar to vicilin), and α-conglutin (similar to legumin) (Lqari et al 2004;Sujak et al 2006;Duranti et al 2008;Foley et al 2015;Jimenez-Lopez et al 2016). Although the protein content (in mg/g of fresh weight) was comparable in the control and irrigated seeds, differences in the staining intensity of electrophoretically separated protein bands (especially the most strongly stained ones, which correspond to storage proteins) may indicate a possible difference in the quantitative proportions of particular types of storage proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these proteins probably participate in the signal transduction pathways, induce hypersensitivity reaction and strengthen the cell wall and cell membrane ( Ribeiro et al, 2014 ; De Oliveira Dias et al, 2015 ). Jimenez-Lopez et al (2016) have found that the β conglutins facilitate the oxidative burst, while at the same time they prevent its extinguishing and induction of apoptosis. The protective function of δ conglutins is also suggested by their similarity to the alpha-amylase inhibitor of cereal plants ( Duranti et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conglutins β1 and β6 suppressed pathogen‐induced cell death in planta. In addition, they inhibited pathogen‐induced suppression of the plant oxidative burst as determined by protein oxidation in infected plants (Jimenez‐Lopez et al, ), due to increased leves of pathogen‐ ( Sclerotinia sclerotiorum , P. nicotianae ) induced protein oxidation promoted by β1 and β6 while maintaining leaf health. This investigation provides the first demonstration for any NLL vicilin (β‐conglutins) of induced protection against pathogen attack.…”
Section: Agricultural Benefits Of Nll β‐Conglutins: Fighting Against mentioning
confidence: 99%